Minimal-Resource Home Exercise Program Improves Activities of Daily Living, Perceived Health Status, and Shortness of Breath in Individuals with COPD Stages GOLD II to IV - Vanessa Joaquim Ribeiro Moço; Aline Almeida Gulart; Agnaldo José Lopes; Arthur de Sá Ferreira; Luis Felipe da Fonseca Reis (COPD, 2023)
Home exercises (HE) with minimal resources seem to be useful in individuals with COPD. The objective was to evaluate the effects of HE, on activities of daily living (ADL), dyspnea, on the health status(CAT) and quality of life (HRQoL) of individuals with COPD GOLD II to IV. Quasi-experimental study of the effects of HE, for 2 months, 3 times a week. Individuals with COPD(n = 45) were recruited, 37 started the protocol(9 did not complete it). 28 individuals (mean age 62.04 ± 5.8 years, FEV1: 44.7 ± 2.25%, FEV1/FVC 59.8 ± 6.9%) were evaluated before and after training. We observed improvements in the ADL-Glittre (4.9 ± 1.4 vs 3.9 ± 1.1 min; mean difference: −0.9 ± 0.2 min [95%CI: −1.3 to −0.2]; p = 0.008), as well as the mMRC score(2.8 ± 1.1 vs 2.07 ± 0.81; mean difference: 0.7 ± 0.3 [95%CI: −1.20.18 to −0.2]; p = 0.009), and in the CAT (25.6 ± 4.8 vs 18.9 ± 3.1; mean difference: −6.6 ± 3.4 [95%CI: −10.6 to −1.6]; p = 0.042). Analyzing the mean change before and after the intervention, a weak correlation was observed between ADL-Glittre and mMRC (r = 0.35; [95% CI 0.09; 0.56]; p = 0.009); moderate between ADL-Glittre and CAT (r = 0.52; [95% CI 0.30; 0.69]; p < 0.001) and between ADL-Glittre and SGRQ (r = 0.50; [95% CI 0 .27; 0.67]; p < 0.001). Individuals with COPD can benefit from HE performed autonomously and with minimal resources, as this proposal improves functional capacity for ADL, health perception and dyspnea.